2014
DOI: 10.1108/ijpsm-11-2012-0160
|View full text |Cite
|
Sign up to set email alerts
|

Management in hospitals

Abstract: Purpose-The hospital sector has expanded in Norway with reforms and a strong demand for better management. In this article, we examine: 1) how this has affected physicians and nurses in management, 2) how management roles in hospitals are changing, and 3) how these two professions are tackling their new roles. Methodology-The article presents a review of the secondary literature and a case study undertaken in the spring, 2012. Findings-In Norway, two reforms have been introduced aimed at creating stronger mana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 23 publications
2
9
0
Order By: Relevance
“…Consequently, FLNMs can choose to maintain both roles and to balance them by emphasising one role and establishing role distance from the other, or they can withdraw from the role of nurse entirely to cope with organisational demands and avoid role conflict. The latter strategy is rarely recognised but may correspond to findings suggesting that nurses grasp the opportunity for social mobility to pursue personal goals (Forbes and Hallier, 2006; Nordstrand Berg and Byrkjeflot, 2014). Nevertheless, this study supports the implementation of the concept of roles, as proposed by Goffman, as point of departure for further studies involving FLNMs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, FLNMs can choose to maintain both roles and to balance them by emphasising one role and establishing role distance from the other, or they can withdraw from the role of nurse entirely to cope with organisational demands and avoid role conflict. The latter strategy is rarely recognised but may correspond to findings suggesting that nurses grasp the opportunity for social mobility to pursue personal goals (Forbes and Hallier, 2006; Nordstrand Berg and Byrkjeflot, 2014). Nevertheless, this study supports the implementation of the concept of roles, as proposed by Goffman, as point of departure for further studies involving FLNMs.…”
Section: Discussionmentioning
confidence: 99%
“…In other studies, the strategies of FLNMs were to regard increased managerial accountability as an advantage or opportunity for an alternative career (Forbes and Hallier, 2006; Johansen, 2009) and therefore preferred the role of manager. After management reforms in Norwegian hospitals, Nordstrand Berg and Byrkjeflot (2014), for example, found that nurses readily adjusted to the new role and perceived management as an opportunity for a new career. Finally, when organisational demands or struggles with role conflict become stressful, FLNMs can respond by withdrawing from their position as managers.…”
Section: Introductionmentioning
confidence: 99%
“…But Swedish examples mirror international examples, showing that although physicians assume limited organizational responsibilities and tend not to see themselves as managers, they become more powerful physicians in their combined role (Andersson 2015;Cregård & Eriksson 2015;Öfverström 2008). Nurses who become health care managers change more than physicians do; their managerial role becomes a career step (Berg & Byrkjeflot 2014), and they substantially integrate their professional and organizational roles (Blomgren 1999(Blomgren , 2003. This role redesign can change the relationships between professions; nurse-managers can challenge physicians -a situation that would be nearly impossible based solely on their professional roles (Berg & Byrkjeflot 2014).…”
Section: Trend 2: Increasing Professional Stratificationmentioning
confidence: 99%
“…Nurses who become health care managers change more than physicians do; their managerial role becomes a career step (Berg & Byrkjeflot 2014), and they substantially integrate their professional and organizational roles (Blomgren 1999(Blomgren , 2003. This role redesign can change the relationships between professions; nurse-managers can challenge physicians -a situation that would be nearly impossible based solely on their professional roles (Berg & Byrkjeflot 2014).…”
Section: Trend 2: Increasing Professional Stratificationmentioning
confidence: 99%
“…However, only a small proportion of nurses apply for management positions. Clinicians' decisions to enter management positions seem to be influenced by pressure from colleagues, managers, and other important persons (Berg & Byrkjeflot, 2014;Spehar, Frich, & Kjekshus, 2012). It is surprising, based on the importance of nurse manager influence on organizational outcomes (Lavoie-Tremblay, Fernet, Lavigne, & Austin, 2016;Morsiani, Bagnasco, & Sasso, 2017), how little research has been conducted into Registered Nurses' motives and reasons for embarking on a career in management (Bondas, 2006;Spehar et al, 2014;Wong et al, 2013).…”
Section: Introductionmentioning
confidence: 99%